A comparison study of deep muscle sparing transverse rectus abdominis musculocutaneous flap for breast reconstruction. Issue 7 (25th February 2019) - Tokumoto, Hideki; Akita, Shinsuke; Arai, Minami; Kubota, Yoshitaka; Kuriyama, Motone; Mitsukawa, Nobuyuki
Abstract : Background: Breast reconstruction by deep inferior epigastric perforator flap (DIEP) involves only little rectus abdominis muscle sacrifice. However, the operative procedure may get complicated. We propose here a novel method involving two adjacent perforators and requiring the addition of only the superficial muscle to the flap. This novel technique, termed "deep muscle sparing transverse rectus abdominis musculocutaneous flap (DMS‐TRAM), " was compared to DIEP and MS‐TRAM groups. Methods: The subjects were 70 patients. The indication of DMS‐TRAM was the distance between two perforators penetrating the deep fascia was <3 cm, and the two perforators ran through the superficial layer of the muscle until they became confluent. All patients were evaluated by contrasting computed tomography. The data of age, body mass index, flap volume, operative time, blood loss, laterality, immediate reconstruction, prior radiation, smoking, re‐exploration, total flap necrosis, partial fat necrosis, and abdominal bulging were compared. Ultimately, DMS‐TRAM was applied in 20 subjects (28.6%), DIEP in 31 (44.3%), and MS‐TRAM in 19 (27.1%). Results: The volume of blood loss in the DIEP group was significantly higher than that in the DMS‐TRAM group (328 ± 182 vs 454 ± 217 mL, p = 0.02), the other factors did not significantly influence. The rate of fat necrosis in DIEP tended to be high (10.0% vs 22.6%, p = 0.22). Conclusions: Because DMS‐TRAM could preserve the deep muscle and penetrating side of intercostal nerve, it could be performed less sacrifice and there were few bleeding and partial necrosis at the same level as MS‐TRAM. DMS‐TRAM was effective in the applied cases.